What is formative assessment? Conceptualisation and level of knowledge of basic education teachers - Maite Zubillaga-Olague; Laura Cañadas; Jesús Manso (Revista Española de Pedagogía)
For educational research and practice, it is vital to identify how much teachers believe they know about formative assessment, as well as their ideas of the concept. However, there has been little research in this area. Therefore, this research aims to: (1) analyse teachers’ perceived level of knowledge of the concept formative assessment, establishing whether there are statistically significant differences according to the educational level at which they teach, the training in assessment they have received, the number of training activities on assessment they have completed, and their years of teaching experience; and (2) to analyse teachers’ theoretical conception of formative assessment. A mixed design was used with 713 teachers from primary education (39.1%) and secondary education (60.9%). The #EvalFormEPESO questionnaire was used to collect information. Specifically, the item about the level of knowledge of the concept formative assessment and an open-ended question requesting its definition. The results show statistically significant differences in the level of knowledge of the concept formative assessment depending on the variables studied. Moreover, the definitions teachers provided show incomplete or erroneous conceptions.